Evaluation of Gas Migration and Rock Damage Characteristics for Underground Nuclear Waste Storage Based on a Coupled Model. (27th June 2018) - Xue, Yi; Dang, Faning; Shi, Fang; Li, Rongjian; Cao, Zhengzheng
Abstract : In the deep geological repository of nuclear waste, the corrosion of waste generates gas, which increases the storage pressure, changes the properties of the rock strata, and affects the stability of nuclear waste repository. Therefore, it is of great importance to understand the gas migration in the engineering barrier and the potential impact on its integrity for the safety assessment of nuclear waste repository. A hydro-mechanical-damage model for analyzing gas migration in sedimentary rocks is established in this paper. On the basis of which, a set of coupled formulas for the coupling of gas migration in rock mass is established. The model considers the characteristics of gas migration in sedimentary rock, especially the microcracks caused by the degradation of elastic modulus and damage, and the coupling between the rock deformation and failure of fractures. The numerical simulation of gas injection test is beneficial to understand the mechanism of gas migration process in sedimentary rock.